A TEM and EELS study of carbon in a melt fragment from the Gardnos impact structure. (29th August 2019) - Lindgren, Paula; Hallis, Lydia; Hage, Fredrik S.; Lee, Martin R.; Parnell, John; Plan, Anders; Doye, Alistair; MacLaren, Ian
Abstract: A carbon‐rich melt fragment from the Gardnos impact structure has been studied for a better understanding of the preservation and structural form(s) of carbon that have been processed by impact melting. The carbon was analyzed in situ in its original petrographic context within the melt fragment, using high‐resolution techniques including focused ion beam‐transmission electron microscopy and electron energy loss spectroscopy. Results show that the carbon is largely uniform and has a nanocrystalline grain size. The Gardnos carbon has a graphitic structure but with a large c/a ratio indicating disorder. The disorder could be a result of rapid heating to high temperatures during impact, followed by rapid cooling, with not enough time to crystallize into highly ordered graphite. However, temperature distribution during impact is extremely heterogenous, and the disordered Gardnos carbon could also represent material that avoided extreme temperatures, and thus, it was preserved. Understanding the structure of carbon during terrestrial impacts is important to help determine if the history of carbon within extraterrestrial samples is impact related. Furthermore, the degree of preservation of carbon during impact is key for locating and detecting organic compounds in extraterrestrial samples. This example from Gardnos, together with previous studies, shows that not all carbon is lost to oxidation during impact but that impact melting can encapsulate and preserve carbon where it is available.